Sinonasal Symptoms and Self-Reported Health before and after Endoscopic Pituitary Surgery—A Prospective Study - Hallén, Tobias; Olsson, Daniel S; Farahmand, Dan; Esposito, Daniela; Olofsson, Ann-Charlotte; Jakobsson, Sofie; Jakobsson Ung, Eva; Sahlstrand-Johnson, Pernilla; Johannsson, Gudmundur; Skoglund, Thomas; Bergquist, Henrik (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Despite the limited invasiveness of endoscopic transsphenoidal surgery (ETSS), some degree of nasal structure destruction is unavoidable. Our objective was to evaluate sinonasal morbidity and self-reported health before and 6 months after ETSS for pituitary tumors, and to identify possible predictive factors for deterioration in sinonasal health.Design Prospective observational cohort study.Setting University tertiary referral hospital.Participants Totally 109 consecutive adult patients undergoing ETSS for pituitary tumors between 2015 and 2019.Main Outcome Measures Sinonasal symptoms and self-reported health before and 6 months after ETSS, assessed by the Sinonasal Outcome Test (SNOT-22) and the EQ-5D questionnaire. Predictive factors for postoperative deterioration in sinonasal symptoms.Results The overall SNOT-22 score did not change, but the score of the rhinologic domain of SNOT-22 worsened from 6.0 ± 5.9 before to 8.0 ± 7.4 6 months after surgery (p = 0.011). The EQ-5D visual analog scale improved from 64.0 ± 22.9 before to 71.1 ± 18.7 6 months after surgery (p = 0.00088). Univariate and multivariable regression analyses showed that prior sinonasal surgery was associated with a significant worsening in rhinologic symptoms 6 months after surgery (p = 0.046 and p = 0.020, respectively).Conclusions Although self-reported overall health improved, significant deterioration of rhinologic symptoms was seen 6 months after ETSS. This information is important for preoperative patient counselling. Further refinement of the surgical technique and follow-up strategies to reduce postoperative sinonasal morbidity could be of value, especially in patients who have undergone prior sinonasal surgery.
Keywords: endoscopic transsphenoidal surgery; pituitary tumors; sinonasal health; quality of life